Implementasi Media Audio-Visual dalam Pembelajaran Istima‘ - Rizka Sari; M Muassomah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2020)
Listening is a basic human ability which is possessed from the beginning of his birth until throughout his life. However, at the level of language learning there is a low level of student interest in learning specifically. For this reason, this study aims to describe the process of implementing the Audio-visual method in special learning for third-semester students of Arabic education at the Bani Fatah Islamic Institute in Jombang. This type of research is a qualitative descriptive study using observation and documentation instruments. The subject and object of this research are the third semester students of Arabic education at the Bani Fatah Islamic Institute in Jombang. The results of this study indicate, istima 'learning process with audio-visual methods that have been arranged very well, namely: a) lecturer planning by preparing appropriate material b) students listening to the video being watched c) students write mufrodat known based on video d) students conclude the story in the video using Arabic e) students take wisdom from the video watched f) evaluation in this study is divided into two: first, written evaluation (students collect mufrodat notes of listening results), second , oral evaluation (students directly speak Arabic in giving conclusions and lessons from the video). In implementing learning specifically using this audio-visual method, it has changed the atmosphere of learning more interesting and increased the activeness of students in learning.